Soil Bacterial Community Responses to N Application and Warming in a Qinghai-Tibetan Plateau Alpine Steppe - Mu, Zhiyuan; Dong, Shikui; Li, Yaoming; Li, Shuai; Shen, Hao; Zhang, Jing; Han, Yuhui; Xu, Yudan; Zhao, Zhenzhen (Frontiers in Ecology and Evolution, 2021)
Nitrogen deposition and climate warming can alter soil bacterial communities. However, the response of soil bacteria in an alpine steppe to these changes is largely unknown. In this study, a field experiment was performed on the northeastern Qinghai-Tibetan Plateau to determine the changes in soil bacterial communities of alpine steppes in response to nitrogen application and warming. The experiment consisted of four treatments, namely no-N application with no-warming (CK), N application (8 kg N ha−1 year−1) with no-warming (N), warming with no-N application (W), and N application (8 kg N ha−1 year−1) with warming (W&N). This study aimed to investigate (1) the changes in soil bacterial diversity and community structure under simulated nitrogen deposition and warming conditions, and (2) the key environmental factors responsible for these changes. Based on the results, soil bacterial diversity and community composition did not change significantly in the short term. Warming had a significant effect on overall bacterial composition, rare species composition, and individual bacterial taxa. Besides, the interaction between nitrogen application and warming had a significant effect on community β-diversity. Above-ground plant variables were highly correlated with bacterial community characteristics. Nitrogen application and warming did not significantly alter the distribution range of the bacterial community. Overall, this study suggests that soil bacterial communities can remain relatively stable at the level of simulated nitrogen application and warming and that short-term climatic changes may have no significant impacts on soil bacterial communities.